Benchmarking the Oxygen Reduction Electroactivity of First‐Row Transition‐Metal Oxide Clusters on Carbon Nanotubes. Issue 14 (27th December 2017) - Wu, Kuang‐Hsu; Allen‐Ankins, Mikaela; Zeng, Qingcong; Zhang, Bingsen; Pan, Jian; Zhang, Jiayun; Su, Dang‐Sheng; Gentle, Ian R.; Wang, Da‐Wei
Abstract: Transition‐metal oxide/nanocarbon hybrids are known to deliver a cooperative oxygen reduction reaction (ORR) with a synergistic effect of the hybrid interface. This work assesses a series of first‐row transition‐metal oxides in the form of surface‐confined clusters on carbon nanotubes, as a mimic of fully exposed hybrid interfaces, providing an activity benchmark for hybrid catalysts. Among the selected metal oxides, MnO x and CoO x are found to be the most active first‐row transition‐metal oxide clusters for the ORR, given their excellent peroxide‐reducing capability at low overpotential. FeO x and CuO x are also active for the same role, except their peroxide‐reducing activity is only activated with substantial overpotential. Other metal oxides (NiO x and ZnO x ) do not appear to show any activity toward the ORR, even with an integrated interface as a source for the possible synergistic effect. Abstract : Reduced to tears : Surface‐confined first‐row transition‐metal oxide clusters on nanocarbons express different cooperative behavior for the oxygen reduction reaction, which is mainly associated with the peroxide‐reducing capability.